2009
DOI: 10.1303/aez.2009.85
|View full text |Cite
|
Sign up to set email alerts
|

Possible involvement of proteinaceous and non-proteinaceous trehalase inhibitors in the regulation of hemolymph trehalose concentration in Bombyx mori

Abstract: The midgut of the silkworm Bombyx mori contains two types of trehalase: soluble and membrane-bound. The trehalose concentration in larval hemolymph remains substantially high through the feeding period of the last (fifth) larval instar, despite appreciable trehalase activity through this period. We found that B. mori larval hemolymph contains two types of trehalase inhibitor, a proteinaceous inhibitor (inhibitor-P) and an inhibitor that is extractable with methanol and ethanol (inhibitor-M). Both inhibit the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…The regulation of serum glucose levels by insulin and glucagon in mammals is parallel to the regulation of hemolymph carbohydrate availability in insects. In Eri silkworms and other lepidopterans, incorporated fatty acids are converted and stored as diacylglyceride in lipophorin, amino acids in storage proteins, and sugars in trehalose, mostly in the hemolymph [ 30 , 31 ]. Hemolymph trehalose concentration is up-regulated by a hypertrehalosemic hormone (HTH), which has been isolated from corpora cardiac (CC) of various orders of insect, and down-regulated by a hypotrehalosemic factor in brain extracts in Calliphora erythrocephala and Phormia regina [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulation of serum glucose levels by insulin and glucagon in mammals is parallel to the regulation of hemolymph carbohydrate availability in insects. In Eri silkworms and other lepidopterans, incorporated fatty acids are converted and stored as diacylglyceride in lipophorin, amino acids in storage proteins, and sugars in trehalose, mostly in the hemolymph [ 30 , 31 ]. Hemolymph trehalose concentration is up-regulated by a hypertrehalosemic hormone (HTH), which has been isolated from corpora cardiac (CC) of various orders of insect, and down-regulated by a hypotrehalosemic factor in brain extracts in Calliphora erythrocephala and Phormia regina [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that the utilizable pathways of trehalose were inhibited by the potency of DNJ. It is known that the trehalose concentration in the hemolymph is regulated homeostatically in the short term (several minutes and hours) and influences insect development in the long term (days and months) [ 30 , 34 , 36 , 37 ]. Meanwhile, as the main source of glucose, trehalose may be the key intermediate regulatory product and the disaccharide can be rapidly utilized as an energy source when insects are hungry [ 34 , 38 ].…”
Section: Discussionmentioning
confidence: 99%